NEW TREATMENT OPTION FOR ESOPHAGOGASTRIC ANASTOMOTIC LEAK: A CASE REPORT - M. M. Davydov; A. G. Abdullaev; O. A. Malikhova; A. V. Tsigankova (Сибирский онкологический журнал)
The formation of esophagogastric anastomosis has a long history due to the search for the most reliable and safe fistula. The use of invagination anastomosis, proposed in the early 90s by Professor M.I. Davydov, fully met all the requirements, allowing significantly improve the quality of life of patients and significantly reducing the frequency of failure of the anastomoses to 0.5%.Case description. We present the case of proximal gastric cancer invading the lower thoracic esophagus. The patient underwent proximal subtotal gastric and lower thoracic esophageal resection using the combination of a laparotomy and right thoracotomy. Contrast radiography performed on day 11 after surgery revealed esophagogastric anastomotic leak. The patient underwent urgent surgery.Conclusion. This article presents a new treatment option for esophagogastric anastomotic leak by using endoscopic transesophageal clipping of the defect in combination with sanitation and drainage of the pleural/mediastinsl cavity. The proposed technique can be considered as a minimally invasive treatment method and can be used in any surgical clinic.